The dynamics of the economic cycle with duration dependence: Further evidence from Jordan - Huthaifa Alqaralleh; Radi Adayleh (Cogent Economics & Finance, 2019)
In this article, we investigate the effectiveness of the credit facilities and foreign trade to combat the cycle duration in the industrial production index. The turning point methodology of Harding and Pagan was adapted to formulate the economic cycle. Using the industrial production index of the Jordanian economy over the months from January 2000 to December 2017, the Logit model was used to test for duration dependence, with the credit facilities and net export included as controls. We find that industrial production index expansions and contractions have positive duration dependence, since their exit probabilities increase with duration. These results first help policy-makers to predict the length of economic cycles and to use these factors to reduce the consequences of the contraction. Second, the fact that duration is significant for the expansion phase could become a useful indicator in predicting the length of an economic cycle. The asymmetric nature of our duration dependence findings is striking.
Keywords: 330; duration dependence; economic cycles asymmetry; logit model; turning points methodology